Moving from an L1 to an L2 Setting: Exploring Parents’ Motivation for Raising Children Bilingually - Novi Rahayu Restuningrum (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2017)
This paper explores the change in parents’ motivation for wanting their children to be bilingual.Derived from a larger study done between 2011-2015, the paper portrays how parents who, at thetime of data collection resided in Australia, changed motivation for communicating with theirchildren bilingually. Evolving from my personal experience and supported by data from tworesearch participants with similar experience, the paper presents an explanatory discussion onhow parents changed motivation for raising children bilingually, which is due to the change ingeographic setting.Using auto-ethnographic approach, I discuss the shifts of motivation that implicate especially inthe preferences for relative emphasis on L1 and L2, to correspond to the change in thesociolinguistic set-up due to the different settings a family has moved to. The early reason whyparents want their children to be able to communicate in two languages in the period priorgeographic movement from countries where English is a foreign language has changed after theylive in Australia. Parents had been motivated to make their children bilingual when they are inthe non-English-speaking contexts because they want their children to catch up with theglobalised world communication, while their main reason for having bilingual children after theylive in Australia is to maintain their heritage culture and language.This paper is expected to enhance the discussion in the field of bilingualism, especially aboutparents’ motivation for children bilingualism, which extends the discussion in other research.